THE EFFECT OF SOCIAL MEDIA TIKTOK ON INCREASING ISLAMIC KNOWLEDGE AMONG STUDENTS - Zannuby Al Izzami; Wahyunengsih Wahyunengsih; Alvin Faiz Al-Farizi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The purpose of this study was to examine the effect of Tiktok social media on increasing Islamic knowledge among students. The object of this research is the students with the number of participants involved are 43 students from 20 universities. Data collection was carried out by a questionnaire consisting of 24 questions. The data collection process is carried out using the Google form platform method. The results showed that quantitatively the students had a positive influence between the influence of Tiktok and Islamic knowledge. In this study, the results showed the numbers 0.70-0.140 which means the effect is in the medium effect. Meanwhile, it is measured using psychological and related indicators to see the effect of Tiktok and Islamic knowledge among students using the SPSS Pearson statistics. Keywords: : Social Media, Influence, Knowledge